2015
DOI: 10.1002/2015jb012437
|View full text |Cite
|
Sign up to set email alerts
|

Critical evaluation of state evolution laws in rate and state friction: Fitting large velocity steps in simulated fault gouge with time‐, slip‐, and stress‐dependent constitutive laws

Abstract: The variations in the response of different state evolution laws to large velocity increases can dramatically alter the style of earthquake nucleation in numerical simulations. But most velocity step friction experiments do not drive the sliding surface far enough above steady state to probe this relevant portion of the parameter space. We try to address this by fitting 1–3 orders of magnitude velocity step data on simulated gouge using the most widely used state evolution laws. We consider the Dieterich (Agin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
132
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(141 citation statements)
references
References 36 publications
8
132
1
Order By: Relevance
“…In this study we adopt the "slip-law," which is most consistent with laboratory experiments (e.g., Bhattacharya et al, 2015): In this study we adopt the "slip-law," which is most consistent with laboratory experiments (e.g., Bhattacharya et al, 2015):…”
Section: Rate-and-state Friction Modelmentioning
confidence: 76%
“…In this study we adopt the "slip-law," which is most consistent with laboratory experiments (e.g., Bhattacharya et al, 2015): In this study we adopt the "slip-law," which is most consistent with laboratory experiments (e.g., Bhattacharya et al, 2015):…”
Section: Rate-and-state Friction Modelmentioning
confidence: 76%
“…The transition under the aging law occurs at asperity sizes between two nucleation length scales L c and L ∞ , defined in Rubin and Ampuero (2005), and is broader at higher a/b because L c /L ∞ ∼ 1/(1 − a/b). However, the L ∞ length is irrelevant under the slip law (Ampuero and Rubin 2008), which is the state evolution law adopted here because it is more consistent with laboratory experiments with large velocity jumps, large enough to model the propagating front of slip transients (Bhattacharya et al 2015). Simulation results presented by Luo (2018) indicate that the width of the transition is more fundamentally affected by the range of scales of heterogeneity than by the choice of state evolution law.…”
Section: Resultsmentioning
confidence: 93%
“…The state variable θ evolves with time, as described by empirical evolution laws. Here we adopt the so-called "slip law", the state evolution law that is most consistent with laboratory experiments (Bhattacharya et al 2015):…”
Section: Model Definitionmentioning
confidence: 99%
“…For the Slip law, recent results show that it unequivocally produces extraordinary good fits to velocity step experiments, but it is not able to match the SHS data to an acceptable extent (Bhattacharya et al, , ). It was also criticized for lacking a clear physical background in the construction of the state variable compared with the Aging law (e.g., Ikari et al, ), although various attempts have been made over the years to help the empirical law find proper physical basis (e.g., Aharonov & Scholz, ; Hatano, ; Sleep, ).…”
Section: Introductionmentioning
confidence: 99%
“…Simulations and inversions for velocity steps (data from Penn State University) and SHS (Beeler et al, , data) experiments are conducted using this new model. For SHS, two kinds of inversions are tried: only fitting the stress peaks and minima, a convenient approach in fitting SHS data (e.g., Beeler et al, ; Bhattacharya et al, ), and inverting the entire finite stress series from the start of the hold till the end of reslide, which is a more difficult approach but also has been adopted by many successful efforts (e.g., Marone, ; Marone & Saffer, ; Niemeijer et al, , ). Nevertheless, to the best of our knowledge, no previous studies have shown the result of fitting multiple finite SHS stress series together using the same parameters, and in the current study we made a first attempt.…”
Section: Introductionmentioning
confidence: 99%